PENGARUH LINGKUNGAN KERJA, MOTIVASI, DAN KOMPENSASI TERHADAP KINERJA KARYAWAN PADA CV. NADIS HERBAL - I Gede Adi Santosa; Made Ika Prastyadewi; I Nyoman Resa Adhika (Program Studi Manajemen Fakultas Ekonomi dan Bisnis UNMAS, 2023)
Employee performance is the result of the abilities and skills and hard work done by employees in order to achieve optimal results for the company. Therefore, to get good employee performance, company management needs to pay attention to factors that affect employee performance, such as work environment, motivation, and compensation. The research objective was to determine the effect of the work environment, motivation, and compensation on employee performance at CV. Nadis Herbal. This research was conducted at CV. Nadis Herbal using a sample of 35 employees. The sampling technique used is the census method. Data collection was carried out through observation, interviews and questionnaires. The data analysis technique used was multiple linear regression analysis with a significance level of 5% which was processed using SPSS version 25 software. The results showed that the work environment, motivation and compensation had a positive and significant effect on employee performance at CV. Nadis Herbs. Suggestions for further research in order to develop this research by adding other variables that can affect employee performance.